APPRAISAL CRITERION QUALITY WORKERS PLACES ENTERPRISE INDUSTRY, TRANSPORT AND TECHNICAL SERVICES - Petr Petrovich Gladky (Вестник Северо-Кавказского федерального университета, 2022)
Methods of complex certification systems “human-technique” workers places and models management parameters condition workers places and professionals qualification level of workers, are the basis of the mechanism of development management system workers places in enterprises.